2017
DOI: 10.1107/s2414314617008689
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 2-{[(6S*,7R*,8S*)-7-acetyl-8-(4-chlorophenyl)-4-cyano-6-hydroxy-1,6-dimethyl-5,6,7,8-tetrahydroisoquinolin-3-yl]sulfanyl}acetate

Abstract: In the title compound, C 23 H 23 ClN 2 O 4 S, the 4-chlorophenyl ring is inclined to the pyridine ring of the isoquinoline group by 71.86 (13) . In the crystal, molecules are linked by pairs of O-HÁ Á ÁO hydrogen bonds, forming inversion dimers, which stack along the b-axis direction. The methyl acetate group attached to the S atom is disordered over two sites in a 50:50 ratio, which appears to prevent close intermolecular contacts between the methyl groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…The absolute configurations of the three chiral centers of this isomer are detected by studying the X-ray diffraction of the single crystal of compounds 3a – c . The previous studies confirmed 6 S , 7 R , and 8 S configurations for the three chiral centers of compounds 3a – c . …”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The absolute configurations of the three chiral centers of this isomer are detected by studying the X-ray diffraction of the single crystal of compounds 3a – c . The previous studies confirmed 6 S , 7 R , and 8 S configurations for the three chiral centers of compounds 3a – c . …”
Section: Resultssupporting
confidence: 65%
“…According to the crystal structure data provided by Dyachenko et al . and Mague et al, , for compounds 3a – c , the cyclohexene ring presented in half chair conformation and both acetyl and hydroxyl groups were in the same direction. Hence, the condensation of the acetyl group of compound 6a with hydrazine derivatives may give the corresponding hydrazone intermediates A , which undergo intramolecular cycloaddition reaction according to the Felkin–Ahn model to give pyrazoloisoquinolines 11a , b rather than 12a , b .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations